Natural Dyes - Perrin Ak&#231, E.; Kumbasar, akoca (IntechOpen, 2011)
Textile materials without colorants cannot be imagined and according to archaeological evidence dyeing has been widely used for over 5000 years. With the development of chemical industry all finishing processes of textile materials are developing continuously and, ecological and sustainable production methods are very important nowadays. In this book you can be find the results about the latest researches on natural dyeing.